Analysis of Child Rights Violation: Forced Marriage Underage and Collaborative Practice - Ika Purnamasari (Jurnal Kesehatan, 2021)
Children's rights are part of human rights that must be guaranteed, protected and fulfilled by parents, family, community, state, government and local government. This article discussed the analysis of a case of violation of children's rights in the form of forced marriage to a child. The case description is an 11-years old girl forced to marry a 50-years old man. The child was bleeding and frightened and then the child was admitted to a hospital. The question that arises based on the description of the case is "How is the collaborative practice in handling the child while in hospital treatment in terms of the Child Protection and Patient Safety Law?". The analytical method used in this case description was a literature study that focuses on reviewing legal aspects, patient safety and collaborative practice in handling the case. The results of the analysis show that in this case there has been a violation of the Child Protection Law, the child must receive safety during treatment and receive collaboration from multi-disciplinary professions. Every child has the right to grow and develop according to his/her age safely and in accordance with his dignity as a human being.